2011
DOI: 10.1002/jor.21393
|View full text |Cite
|
Sign up to set email alerts
|

Humeral cementless surface replacement arthroplasties of the shoulder: An experimental investigation on their initial fixation

Abstract: Cementless surface replacement arthroplasties are increasingly being used to treat arthritic humeral heads. These implants are designed to provide narrow bone resection, making a later revision easier. However, no clear evidence exists as to whether their initial fixation is sufficient for bony ingrowth. The aim of our in vitro study was to characterize the relative micromotion of two resurfacing implants with essentially different bone-facing geometries. Both systems were implanted into 10 human humeral speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
(34 reference statements)
1
13
0
Order By: Relevance
“…None of the implants showed connective tissue formation at larger proportions of the interface between the implant surface and bone. This suggests sufficient primary stability and is in line with in‐vitro biomechanical CSRA studies …”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…None of the implants showed connective tissue formation at larger proportions of the interface between the implant surface and bone. This suggests sufficient primary stability and is in line with in‐vitro biomechanical CSRA studies …”
Section: Discussionsupporting
confidence: 84%
“…However, in this study no significant differences between the crown and stem fixed geometries or the coatings of the four manufacturers were observed. Similarly, Jacubowitz et al reported in their biomechanical study only about small differences in the micromotions when evaluating the primary stability of the crown and stemmed fixed geometries …”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Adequate fixation to the host bone of the proximal humerus is a critical factor in the success of resurfacing. [13] Glenoid loosening is a significant factor in failure of total shoulder replacement,[14] with the majority of revision arthroplasty performed to address this issue. [15] High temperatures have been noted at the implant glenoid interface[16] and glenoid reaming has been shown to generate high temperatures in vivo , beyond the physiological threshold required to induce osteonecrosis.…”
Section: Introductionmentioning
confidence: 99%